Authentic Assessment for Holistic Learning: Evaluating the Implementation of Formative Practices in Indonesian CBE Classrooms - Ginanjar, Ani Yanti; Anisah, Ani Siti; Munggaran, Silvi Wulan; Lestari, Putri Ayu (Indonesian Scientific Publication, 2025)
This study examines the implementation of alternative assessment practices in Indonesian primary schools within the Competency Based Education (CBE) framework. Guided by the Merdeka Belajar policy, the research focuses on how portfolios, performance tasks, and student-led reflections are integrated into classroom instruction. A qualitative dominant mixed methods design was employed, involving document analysis, observations, interviews, and rubric based performance scoring in three schools representing urban, rural, and remote (3T) contexts. Findings show that alternative assessments enhance engagement, critical thinking, and communication skills when supported by project-based learning and clear rubrics. Digital tools, especially the Platform Merdeka Mengajar (PMM), enabled real-time feedback and differentiated instruction in digitally equipped schools. However, challenges such as teacher workload, rubric inconsistency, and limited digital infrastructure in rural and 3T areas affected implementation fidelity. Teachers with higher assessment literacy were more consistent in applying formative practices and leveraging assessment data for instructional decisions. The study concludes that sustained implementation of alternative assessments requires systemic support including professional development, collaborative planning structures, and equitable access to digital tools. These practices are essential for realizing the goals of CBE and promoting inclusive, student centered learning environments. The research contributes to policy discourse on assessment reform and offers practical insights for teachers, school leaders, and curriculum designers